Gold nanoparticles for the in situ polymerization of near-infrared responsive hydrogels based on fibrin. (December 2019) - Escudero-Duch, Clara; Martin-Saavedra, Francisco; Prieto, Martin; Sanchez-Casanova, Silvia; Lopez, Daniel; Sebastian, Victor; Arruebo, Manuel; Santamaria, Jesus; Vilaboa, Nuria
Abstract: Non-invasiveness and relative safety of photothermal therapy, which enables local hyperthermia of target tissues using a near infrared (NIR) laser, has attracted increasing interest. Due to their biocompatibility, amenability of synthesis and functionalization, gold nanoparticles have been investigated as therapeutic photothermal agents. In this work, hollow gold nanoparticles (HGNP) were coated with poly-l -lysine through the use of COOH-Poly(ethylene glycol)-SH as a covalent linker. The functionalized HGNP, which peak their surface plasmon resonance at 800 nm, can bind thrombin. Thrombin-conjugated HGNP conduct in situ fibrin polymerization, facilitating the process of generating photothermal matrices. Interestingly, the metallic core of thrombin-loaded HGNP fragmentates at physiological temperature. During polymerization process, matrices prepared with thrombin-loaded HGNP were loaded with genetically-modified stem cells that harbour a heat-activated and ligand-dependent gene switch for regulating transgene expression. NIR laser irradiation of resulting cell constructs in the presence of ligand successfully triggered transgene expression in vitro and in vivo . Statement of significance: Current technological development allows synthesis of gold nanoparticles (GNP) in a wide range of shapes and sizes, consistently and at scale. GNP, stable and easily functionalized, show low cytotoxicity and high biocompatibility. Allied to that, GNP present optoelectronic properties that have been exploited in a range of biomedical applications. Following a layer-by-layer functionalization approach, we prepared hollow GNP coated with a positively charged copolymer that enabled thrombin conjugation. The resulting nanomaterial efficiently catalyzed the formation of fibrin hydrogels which convert energy of the near infrared (NIR) into heat. The resulting NIR-responsive hydrogels can function as scaffolding for cells capable of controlled gene expression triggered by optical hyperthermia, thus allowing the deployment of therapeutic gene products in desired spatiotemporal frameworks. Graphical abstract: Image, graphical abstract